A new species of Nogunius Jałoszyński in Japan (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł; Nomura, Shûhei (Zootaxa, 2021)
The genus Nogunius Jałoszyński was proposed to accommodate four species distributed exclusively in Japan: N. sokani Jałoszyński (Okinawa Island), N. aogashimanus Jałoszyński (Aogashima, Izu Islands), N. kerri Jałoszyński (Ishigaki Island), and N. fukuuzanus Jałoszyński (Okinawa Island). A female of an undescribed species collected in mainland Japan, on Shikoku, was also recorded. In the present paper we provide evidence that this interesting and apparently very rare genus occurs also on Kyushu. Nogunius sagaensis sp. n. is described, based on a single male collected in Saga Prefecture, NW Kyushu. Diagnostic characters of all nominal species are compared, and a distribution of Nogunius is summarized.